Dampak Eksploitasi Sumber Daya Alam Dalam Peningkatan Kesejahteraan Masyarakat Perspektif Ekonomi Islam: Studi Pada Tambang Pasir CV Putra Kembar Polewali Mandar - Saad, Muh.; Rukayyah Yunus, Ayu; Muslihati , Muslihati (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2021)
This research is a field research with the type of qualitative research with a descriptive approach. Data collection techniques using direct observation, interviews and documentation. While data analysis used data reduction, presentation and then drawing conclusions. The data examination technique in this study used the data triangulation method. The results of the analysis show that the impact on the community regarding the exploitation of natural resources that occurred in the village of Serangan started from the occurrence of earthquakes, landslides and damage to the ecosystem in the area around the area. In general, the exploitation of natural resources in the village of Serangan and the impact on the community through field observations is very concerning, there has been damage to more than half of the total village of Serangan. In addition to damaging the environment due to mining activities carried out in the village of Serangan, it has also claimed lives, because they are only armed with mining with traditional and makeshift equipment.